PERAN IMAN KATOLIK DALAM REKA-CIPTA BUDAYA: Sebuah Cara Berteologi Dalam Agenda Misi Gereja - Boloawa, Martin Oni (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STPAK St. Yohanes Penginjil Ambon, 2012)
This paper is an attempt of doing theology in the context of our socio-cultural conditions today. The main idea of this article is that faith and culture are closely related. Faith is never arise from or be separated from culture. Faith is expressed in a culture which is a form of a religion. The synthesis between faith and culture is not only a demand of culture but also a demand of faith. Because, faith itself cannot be fully accepted, cannot be entirely understood and will not faithfully lived, if it is separated from culture.